Future Outlook of ATMs in India - Emerging Issues and Possible Solutions - Uppal, R. K. (Indian Journal of Finance, 2010)
Transactions through e-channels cost much less to the banks than the customers reaching the bank. In the post era of IT Act, information technology in different bank groups is continuously increasing. They are providing more facilities through ATMs, I-banking, Tele-banking etc. ATM is one of the best alternative and most popular e-channel available to customers for quick, correct and efficient service at anytime and anywhere. The present paper is devoted to explore the extent of ATMs among all e-channels. Time period taken for the study is 2000-01 to 2006-07 because this period is the eye-witness of infant condition of IT and during the same period, IT became mature. Simple statistical tools like average, standard deviation, co-efficient of variation are used to calculate the efficiency of various bank groups providing the service of ATMs. On the basis of analysis, the paper concludes that the private sector banks are on the top in providing the ATMs services to their customers and have high profitability as compared to other bank groups under the study except foreign banks. The paper suggests some strategies with their possible solutions like spread awareness regarding ATMs and to increase their area and scope to enhance ATMs' services in India, particularly in rural and semi-urban areas.